2019
DOI: 10.1136/injuryprev-2019-043405
|View full text |Cite
|
Sign up to set email alerts
|

Differences in public support for handgun purchaser licensing

Abstract: ObjectiveTo assess whether there are differences in support for handgun purchaser licensing.MethodsWe used data from four waves of online, national polling on gun policy. To estimate differences in support for licensing across groups, we categorised respondents by whether they personally owned a gun, lived in a state with handgun purchaser licensing or lived in a state regulating private sales without a licensing system.ResultsEighty-four per cent of adults living in states with licensing supported the policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Combining survey results from found that 61 percent and 81 percent of gun owners and non-gun owners, respectively, supported handgun purchaser licensing. That said, gun owners living in states with licensing laws were significantly more likely to support the laws than gun owners living in states without such laws (77 percent versus 59 percent) (Crifasi et al, 2020).…”
Section: Licensing and Permitting Requirementsmentioning
confidence: 98%
“…Combining survey results from found that 61 percent and 81 percent of gun owners and non-gun owners, respectively, supported handgun purchaser licensing. That said, gun owners living in states with licensing laws were significantly more likely to support the laws than gun owners living in states without such laws (77 percent versus 59 percent) (Crifasi et al, 2020).…”
Section: Licensing and Permitting Requirementsmentioning
confidence: 98%
“…Though just nine states and the District of Columbia require a license to purchase as of March 2022, these laws are popular. Studies have found high levels of public support for policies requiring prospective gun purchasers to acquire a license from law enforcement (Barry et al 2018(Barry et al , 2019Crifasi et al 2020). In general, "universal background checks"-policies that extend background checks to private transfers-are very popular, even among gun owners (Barry et al 2019).…”
Section: Purchaser Licensingmentioning
confidence: 99%
“…In most cases, the check is facilitated by an FFL: the prospective transferor and transferee work with an FFL to submit the relevant paperwork to the FBI or state agency responsible for NICS checks. The specific process may vary, but these laws create a procedure for private transfers that is almost identical to the process for FFL sales (Crifasi, McCourt, and Webster 2019; Giffords 2022). In theory, this comprehensive background check requirement should more thoroughly keep guns away from those at high risk of harming themselves or others, but studies have found mixed evidence of success.…”
Section: Prohibiting Purchase: Background Check and Licensing Lawsmentioning
confidence: 99%
“…Policy discussion over limiting gun accessibility has recently increased in response to the growing rate of mass shootings and gun homicides. One policy of interest is handgun purchaser licensing, which has had differing levels of support in the United States 5 . In this paper, we consider the effects of the repeal of Missouri's Permit-to-Purchase (PTP) gun licensing law in 2007.…”
Section: Introductionmentioning
confidence: 99%